PHARMACOECONOMICS AS A NEW INSTRUMENT OF PHARMACEUTICAL MARKETING - M. V. Protsenko; N. I. Koroleva (Фармакоэкономика)
A properly conducted pharmacoeconomic study and its results are a new element in the body of evidence for drugs recently introduced into clinical practice. Utilization of pharmacoeconomic analysis results as a new instrument in pharmaceutical marketing lets marketing specialists know what information to convey to health care decision makers and how to bring this information full, correct, and easy to understand.